2001
DOI: 10.1200/jco.2001.19.1.111
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of 18F Fluorodeoxyglucose Positron Emission Tomography in Patients With Non–Small-Cell Lung Cancer: A Prospective Study

Abstract: FDG PET scanning changed or influenced management decisions in 70 patients (67%) with NSCLC. Patients were frequently spared unnecessary treatment, and management was more appropriately targeted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
102
0
5

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 207 publications
(112 citation statements)
references
References 22 publications
5
102
0
5
Order By: Relevance
“…Patients with a primary tumour SUV2 greater than 3.2 after chemoradiation were more likely to relapse (Oku et al, 2002). As with our previous experience with the use of FDG-PET for therapeutic monitoring in lung cancer (Kalff et al, 2001), the current study demonstrated that a local CMR on PET was more common in the primary tumour than a CR on conventional imaging. Although we have shown that a CMR is prognostically significant in lung cancer patients (Mac Manus et al, 2003), the lack of CMR in the metastatic sites, which were present in the majority of patients, limits assessment of the prognostic significance of a local CMR in our cohort.…”
Section: Discussionsupporting
confidence: 67%
“…Patients with a primary tumour SUV2 greater than 3.2 after chemoradiation were more likely to relapse (Oku et al, 2002). As with our previous experience with the use of FDG-PET for therapeutic monitoring in lung cancer (Kalff et al, 2001), the current study demonstrated that a local CMR on PET was more common in the primary tumour than a CR on conventional imaging. Although we have shown that a CMR is prognostically significant in lung cancer patients (Mac Manus et al, 2003), the lack of CMR in the metastatic sites, which were present in the majority of patients, limits assessment of the prognostic significance of a local CMR in our cohort.…”
Section: Discussionsupporting
confidence: 67%
“…Reported frequencies have ranged from 10% to 40% (4)(5)(6)(7)(8)(9)(10)(11)(12). Most of these publications were from single centers that assessed oncologic PET in aggregate or focused on common specific cancers and indications currently covered by CMS for Medicare beneficiaries.…”
Section: Discussionmentioning
confidence: 99%
“…Similar methodology has been used at other institutions to assess the impact of PET on clinicians' intended patient management plans (5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Methodsmentioning
confidence: 99%
“…This imaging mode has been shown by several studies to upstage approximately 30% of patients being considered for radical Table 6 The descriptive statistics of the LCSS scores at baseline and at 3 weeks post CRT High-dose palliative chemoradiotherapy in NSCLC M Michael et al therapy by the detection of unsuspected metastasis. It has also been shown to provide a better correlation with survival vs conventional staging (Dunagan et al, 2001;Kalff et al, 2001;Hoekstra et al, 2003;MacManus et al, 2003). A retrospective study from our institution has also demonstrated that OS correlated with FDG-PET defined metastatic disease burden, for example, 12 months in patients with one metastatic site vs 5 months if greater than one site MacManus et al, 2003).…”
Section: Discussionmentioning
confidence: 77%